2014
DOI: 10.1371/journal.pone.0107103
|View full text |Cite
|
Sign up to set email alerts
|

QTL Analysis and Candidate Gene Mapping for the Polyphenol Content in Cider Apple

Abstract: Polyphenols have favorable antioxidant potential on human health suggesting that their high content is responsible for the beneficial effects of apple consumption. They control the quality of ciders as they predominantly account for astringency, bitterness, color and aroma. In this study, we identified QTLs controlling phenolic compound concentrations and the average polymerization degree of flavanols in a cider apple progeny. Thirty-two compounds belonging to five groups of phenolic compounds were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…Considering the synteny between Prunus and Malus (Dirlewanger et al 2004;, in our progeny, the QTLs detected that control phenolic content were not located in the same genomic regions as in apple (Chagné et al 2012, Verdu et al 2014). Chagné et al (2012) found QTLs for flavonoid and anthocyanin contents on LG16…”
Section: Qtl Analysismentioning
confidence: 79%
See 1 more Smart Citation
“…Considering the synteny between Prunus and Malus (Dirlewanger et al 2004;, in our progeny, the QTLs detected that control phenolic content were not located in the same genomic regions as in apple (Chagné et al 2012, Verdu et al 2014). Chagné et al (2012) found QTLs for flavonoid and anthocyanin contents on LG16…”
Section: Qtl Analysismentioning
confidence: 79%
“…For example, aroma and other volatile compounds were partially mapped onto the Prunus reference map (Illa et al 2011;Eduardo et al 2013) and were analyzed using a high-throughput gas chromatography-mass spectrometry (GC-MS)-based metabolomics approach (Sánchez et al 2012). Some phenolic compounds (pigments) were mapped on the T × E reference map (Ogundiwin et al 2009), and other phenolic compounds (Chagné et al 2012;Verdu et al 2014) and vitamin C (Davey et al 2006) were identified in apple, but to our knowledge no QTLs that control phenolic compounds (including total phenolic, flavonoid, or anthocyanin contents) or vitamin C have been mapped in peach. These antioxidant compounds are important and potentially beneficial to human health because they are involved in the prevention of degenerative diseases such as hypertension, coronary heart diseases, Alzheimer's disease, stroke, and cancer (Boeing et al 2012;Martin et al 2013;Vizzotto et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“… 2012 ; Verdu et al. 2014 ). However, the footprints of selection have been little studied so far in apples compared to annual crops (Yamasaki et al.…”
Section: Introductionmentioning
confidence: 99%
“…Since anthocyanins play a critical role in fruit coloration, molecular mechanism underlying anthocyanin accumulation has recently been extensively studied in apple (Takos et al, 2006a ; Ban et al, 2007 ; Espley et al, 2007 ; Li et al, 2012 ; Xie et al, 2012 ; Chagné et al, 2013 ; Dare et al, 2013 ; Vimolmangkang et al, 2013 ). In contrast, only a few studies have been conducted to investigate molecular basis of proanthocyanidin biosynthesis in apple (Chagné et al, 2012 ; Han et al, 2012 ; Henry-Kirk et al, 2012 ; Verdu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…PAs account for up 80% of the total phenolic compounds in apple, and thus represent the predominant apple antioxidants (Wojdylo et al, 2008 ). More recently, a limited number of quantitative trait locus (QTL) mapping studies have been conducted to understand the genetic basis of PA accumulation in apple, and a major QTL together with several minor QTLs for the content of flavanol monomers and procyanidins and the average polymerization degree of procyanidins have been identified (Chagné et al, 2012 ; Khan et al, 2012 ; Verdu et al, 2014 ). A LAR gene within the major QTL interval is considered as a strong candidate controlling the accumulation of both flavanols and procyanidins (Chagné et al, 2012 ; Khan et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%